The Effect of Audio-Visual Danger Signs of Pregnancy Knowledge of Pregnant Mothers in Work Area Public Health Center Tilango (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Every pregnant woman has a risk to the health of the mother and fetus, for that pregnant women need to be equipped with knowledge about the danger signs of pregnancy, so as to minimize the occurrence of morbidity and mortality that occurs. The purpose of this research is to determine the effect of audio-visual on the danger signs of the knowledge of pregnant women in the working area of the PuskesmasTilango, Telaga District, Gorontalo Regency before and after being given counseling. This method of community service uses the approach of pre-experiment by designing one group pretest-posttest. The Number of samples in this study was as much as 30 respondents as well as data analysis using the Wilcoxon signed rank test. From the result counseling show increase in knowledge of pregnant women before and after being given counseling health about the dangers of pregnancy by using audio-visual. Suggestion: It is hoped that health workers and cadres will be more aggressive in providing counseling and socialization to pregnant women from an early age to avoid risks to pregnant women.